Small scale pig production in Takeo province in a rural area of Cambodia - Wallberg, Emilia (2011)

(untitled)
Cambodia, in Southeast Asia, has tropical monsoonal climate with distinct dry and rain seasons. Many people are poor and live in rural areas. Farmers mainly culture rice, and raise pigs, cattle and poultry as well. During two months, a minor field study was performed in Cambodia. The main purpose was to evaluate the impact of contributions done by projects that started in 2005 and were managed by the local organization CelAgrid. The project´s main objectives were improving animal health, educating people in animal management, improving food security and enhancing families’ annual incomes through sustainable economy. Small scale pig production was part of the field study as well. Another purpose of the present study was to convey newly found knowledge and vital point of views back to farmers participating. After this report is done, a compilation will be given back in their local language. During the practical part of the minor field study, 25 farmers where interviewed in five different villages in Takeo province. In one village, Sras Takoun, some farmers participated in a practical evaluation, by the use of a Participatory Rural Appraisal (PRA-) method. According to results found, annual income had increased and the food security had stabilized since the project started. Farmers learned about animal management; resulting in somewhat improved animal health. In conclusion, CelAgrid reached their purposes. However, there is still a lot to do in the rural areas of Cambodia.